The Influence of Service Quality, Price, and Campus Image on Loyalty Through Student Satisfaction as an Intervening Variable at STIE PEMUDA Surabaya - Lelono Diyah Setiyowati; Slamet Riyadi (Economic and Bussiness Faculty, Dr Soetomo University, 2022)
This study aims to analyze the effect of Service Quality (X1), Price (X2), Image (X3), on Student Loyalty (Y), STIE PEMUDA Students with student satisfaction as an intervening variable. The population in this study were all STIE PEMUDA students, the sampling technique used was stratified random sampling with 119 respondents taking data through a Likert scale model questionnaire. This study uses the Path analysis test with the help of the SPSS For Windows 16.0 computer program. The results of this study indicate that service quality has a positive and significant effect on student satisfaction. Price has a positive and significant effect on student satisfaction. Campus Image has a positive and significant influence on student satisfaction. Service Quality has a positive and significant influence on student loyalty. Price has a positive and significant effect on loyalty. Campus Image has a positive and significant influence on loyalty. Student satisfaction has a negative effect on loyalty. Service Quality has a positive and significant influence on student loyalty through student satisfaction. Prices have a positive and significant effect on student loyalty through student satisfaction. Campus image has a positive and significant influence on student loyalty through student satisfaction.